Изменение гомеостаза при синдроме острого повреждения лёгких (СОПЛ) - Герасютенко, Д. Э.; Герасютенко, Д. Е.; Gerasvutenko, D. E. (My University, 2005)
Пациентам с синдромом острого повреждения лёгких в базисную интенсивную терапию включали малопоточную мембранную оксигенацию крови, которая снижала артериальную гипоксемию, нормализовала показатели гемодинамики, биологической целостности организма и тормозила дальнейшее развитие танатогенеза Пацієнтам з синдромом гострого ушкодження легенів проводили мембранну оксигенацію крові, яка знижувала артеріальну гіпоксемію, нормалізувала показники гемодинаміки, біологічної цілісності організму та гальмувала подальший розвиток танатогенезу Patients with syndrome of lungs acute damage, in condition of resuscitation department are subjected to membrane oxygenation of blood. The aim of this treatment is to increase the partial pressure, to normalize the acid-alcaline condition and to improve the general patient's condition. The increase of partial pressure and arteriovenous difference in oxygen evidence about an adequate oxygen consumption by tissues and the decrease of oxygen duty.
Зміна гомеостазу при синдромі гострого ушкодження легенів (СГУЛ)
Changes of the homeostasis in the syndrome of lungs acute damage
Keywords: синдром острого повреждения лёгких; малопоточная мембранная оксигенация крови; синдром гострого ушкодження легенів; малопоточна мембранна оксигенація крові; syndrome of lungs acute damage; membrane oxygenation of blood